Diagnostic Study of Salmonella typhimurium in Patient and Cattle - Habeeb, Zainab Sami; AL-Shawi, Amil majid; Fathi, Muniem M. (The Iraqi Journal of Veterinary Medicine, 2004)
A total of (150) stool samples were collected from patient with diarrhea in Baghdad hospital and Al - Thahab. Al-Aboiath village. A total of (27) isolates were identified as member of the genous Salmonella, Serotype typhimurium of a percentage of 18 % of the total samples.Another(150) stool sample were collected from suspected calves and cows in some of Baghdad villages and dairy cattle stations The identified isolates as member of Salmonella,serotype typhimurium were (7) at a percentage of 4.5% of the total taken samples. The study extend from December 2001 till May 2002. Different biochemical tests were applied to differentiate the isolates from other enteric micro organism, Including the classical and newly introduced methodologies(i.e.,api 20E) in addition to the type and serotype determination using standard mono specific and polyvalent antisera. All the isolates showed no changes in there characteristic features.